Acceso abierto como bien común y público en Angola colaboración Sur-Sur - Becerril-García, Arianna; Aguado-López, Eduardo; Macedo-García, Alejandro; Neupane, Bhanu; Gungula, Eurico Wongo (Ariadna Ediciones, 2022)
"Open Access as a common and public good in Angola: South-South collaboration" shows the main results achieved in the scope of the cooperation project "Acesso Aberto Angola" and highlights the solidarity between the Global South for the establishment of innovative strategies that allow the scope of new horizons, seeking to accelerate the development and management of scientific knowledge, as well as the transformation potential of science in the search for solutions to problems with which the 21st century has surprised humanity (as is the case of COVID-19), as well as historically unresolved phenomena in countries like Angola, such as the fight against hunger and poverty, desertification and untreated tropical diseases.